2004
DOI: 10.1161/01.str.0000147724.83468.18
|View full text |Cite
|
Sign up to set email alerts
|

Poststroke “Pushing”

Abstract: Background and Purpose-Patients with hemiparetic stroke have impaired balance control. Some patients ("pushers") are resistant to accepting weight on and actively "push" away from the nonparetic side. This research identified pushers from stroke patients with moderate to severe hemiparesis and examined longitudinal changes in symptoms, level of impairment, and functional independence. Methods-Prospective sample of hemiparetic stroke patients (nϭ65) located in Toronto, Canada. Detailed clinical assessments were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0
7

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(50 citation statements)
references
References 25 publications
0
43
0
7
Order By: Relevance
“…Pedersen et al (Pedersen et al, 1996) found an incidence of 5.3 % of PB in all stroke patients who were admitted in study period and 10.4 % of patients without lower extremity paresis on admission, when early death or early recovery were excluded. Danells et al (Danells et al, 2004) found a PB incidence of 23% and 63% among 65 stroke patients with moderate to severe hemiparesis depending on the assessment cutoff. We found 1.5 % of pusher patients among all neurological inpatients of an emergency hospital (Santos- Pontelli et al, 2004), and Lafosse et al (Lafosse et al, 2005) found an incidence of 40 % of left-brain-damaged patients and 52% of right brain damaged patients at a rehabilitation center.…”
Section: Incidencementioning
confidence: 99%
See 4 more Smart Citations
“…Pedersen et al (Pedersen et al, 1996) found an incidence of 5.3 % of PB in all stroke patients who were admitted in study period and 10.4 % of patients without lower extremity paresis on admission, when early death or early recovery were excluded. Danells et al (Danells et al, 2004) found a PB incidence of 23% and 63% among 65 stroke patients with moderate to severe hemiparesis depending on the assessment cutoff. We found 1.5 % of pusher patients among all neurological inpatients of an emergency hospital (Santos- Pontelli et al, 2004), and Lafosse et al (Lafosse et al, 2005) found an incidence of 40 % of left-brain-damaged patients and 52% of right brain damaged patients at a rehabilitation center.…”
Section: Incidencementioning
confidence: 99%
“…A possible gender influence on the incidence of PB was initially suggested (Lafosse et al, 2005). Nevertheless, analysis of several studies performed in large samples of neurologic injured patients found no persistent gender predominance (Danells et al, 2004;SantosPontelli et al, 2004;Lafosse et al, 2005). Paresis of the contralesional extremities seems to be more frequent and more severe in pusher patients than in control encephalic lesioned patients .…”
Section: Demographic and Clinical Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations